REGIONAL CONVERGENCE AND R&D INVESTMENT: APPLIED INVESTIGATION IN PORTUGAL - Guerreiro, Gertrudes (2016)
R&D investments are seen has having an enormous potential impact on the competitive position of regions and perhaps on regional convergence (or divergence) too. The aim of the paper is to study both the localization of R&D investments and regional income distribution among the NUTs 3 regions of Portugal to conclude if these variables are related or not. To study the spatial convergence (approximation) of per capita income (GDPpc) and R&D investments in the regions of Portugal, we use a standard methodology of spatial econometrics. We conclude that regions with higher GDPpc are not the same with the highest concentration of R&D investments, with the exception of the northern coastline. The R&D investments are geographically linked to the network of higher education institutions, especially in the interior regions of the country. The northern regions reveal more dynamic in terms of R&D, which apparently is not felt in the population's standard of living measured by GDPpc.